The impact of social media in conserving African Languages amongst youth in Limpopo Province - Malatji, Edgar Julius (My University, 2019)
This study focuses on the impact of social media towards conserving African languages, particularly Sepedi, Tshivenda and Xitsonga. Social media are given attention to explore their impact in conserving African languages amongst youth. Youth is a suitable group to focus on as they are the future and are thus expected to carry their African languages and pass them on to succeeding generations. This exercise should be done to ensure that African languages should not face extinction in the future. Generally, youth are constant users of social media platforms, hence it is cardinal to investigate their language-usage patterns on social media platforms. The majority of the African youth in South Africa use either one or more of the nine (9) indigenous African languages that are official, namely, isiNdebele, isiXhosa, isiZulu, Sepedi, Sesotho, Setswana, siSwati, Tshivenda, and Xitsonga. Therefore, one would expect speakers of these indigenous African languages to effectively use them on social media, particularly, Facebook, Twitter, and WhatsApp. African language heritage is undoubtedly a valuable resource, however, it needs state resources to develop it further and establish it as a core economic driver on various media platforms. The study employs exploratory and descriptive designs. These designs are appropriate for this study because it permits data to be collected through observations, focus group interviews and questionnaires. Focus group interviews, observations, and questionnaires were used to collect data. Focus group is a data-collection tool for understanding people’s behaviour and attitudes. The researcher moderated three focus groups. One hundred (100) questionnaires were distributed to the participants in this study. These tools are apt for the data-collection process in this study because they assist to discover factors that influence opinions, attitudes, and behaviours. Social media have great potential to conserve the African languages but the speakers of these languages should play a cardinal role in this process. Majority of the youth do not prefer to use the African languages on social media. Conversations on both Facebook and Twitter are dominated by English as youth prefer it ahead of Sepedi, Tshivenda, and Xitsonga. In contrast, youth prefer to use the African languages on WhatsApp because they know their contacts. However, code-switching is used a lot by youth on social media. Despite the fact that Sepedi, Tshivenda, and Xitsonga are not mostly used on Facebook and Twitter they remain relevant and useful amongst their speakers on a daily basis. Nevertheless, there is a need to develop the African languages based social media sites to stimulate their usage on these platforms. Additionally, these languages should be developed to fit the needs of social media.
Thesis (Ph.D. (Media Studies)) -- University of Limpopo, 2019
Keywords: Social media impact; African language conservation; Sepedi, Tshivenda and Xitsonga; Mass media - social aspects; African language